ANALISA USEBILITY DESAIN USER INTERFACE PADA APLIKASI TOKOPEDIA MENGGUNAKAN METODE HEURISTICS EVALUATION - Muhammad Farid Wahyudi, Farid; Popon Handayani (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2023)
The internet is a very popular means of communication and information at this time besides that online applications based on Android or iOS have become the main choice compared to using a web browser to open web pages. Many application developers are starting to focus on application development on the ease of accessing and operating it. Therefore, we need an evaluation of usability through user experience in e-commerce applications. This study measures how satisfied the Tokopedia mobile application is with Tokopedia’s ease of usability based on user reviews through the use of questionnaires and heuristic evaluation guidelines to evaluate the Tokopedia application. And the results of the reliability test each obtained a Cronbach’s alpha value of 0.945, which was greater than the r table value of 0.2068. The results of the t test on the price quality variable obtained a significant value of 0.001 <0.05, so partially there is a positive effect of price quality on customer satisfaction on Tokopedia’s usability. The results of r square show the value (r square) obtained from the study of 0.9431. The r square results mean that 94.3% of the variation in customer satisfaction is the usability of Tokopedia.